Quantification of Anopheles daily sugar feeding rates in Siaya county, western Kenya using Attractive Sugar Baits - Jackline Jeruto Kosgei; Daniel P. McDermott; Seline Omondi; Vincent Moshi; Martin J. Donnelly; Collins Ouma; Prashanth Selvaraj; Angela F. Harris; Julian Entwistle; Feiko O. Ter Kuile; Keith Fraser; Lazaro Mwandigha; et al. (PLoS ONE, 2025)
Background Vector control is an essential component of malaria prevention that has contributed to the reduction in malaria burden since 2000. Although steady progress in malaria vector control has been achieved over the years, the malaria burden remains substantial, underscoring the need for complementary mosquito control tools to further reduce transmission. Attractive targeted sugar baits (ATSBs) are a novel vector control tool under evaluation. The ATSB paradigm leverages the sugar feeding and resting behavior of mosquitoes exposing them to the lethal effect of an added insecticide. Prior to epidemiological trials on ATSBs in western Kenya, validation studies were conducted to assess the levels of mosquito feeding on attractive sugar baits (ASBs), containing uranine dye. This study sought to understand the ATSB deployment required in peridomestic spaces and to determine the daily feeding rates that would be potentially sufficient to impact malaria transmission (based on modelling approaches). The study evaluated whether the deployment of two versus three bait stations per structure led to higher daily feeding rates by local malaria vectors that is consistent with the modelled threshold of 2.5% of all mosquitoes in the target area as a proxy for ATSB efficacy resulting in a 30% drop in clinical incidence in children under 5. Methods The study followed a cross-over design in ten treatment and two control clusters within Rarieda Sub-County, Siaya County, western Kenya. Within each intervention cluster, either two or three ASBs were deployed to all structures in each cluster. After two months, the treatments were switched so that clusters which initially received two ASBs were given three ASBs and vice versa. ASB monitoring was done for four months during the initial crossover trial and then for an additional four months for extended monitoring. Mosquitoes were collected using ultraviolet CDC light traps and Prokopack aspiration indoors and outdoors then identified based on morphological characteristics and screened for fluorescence due to the uranine dye. Molecular species identification was done using polymerase chain reaction and sporozoite infectivity tests by Enzyme-linked immunosorbent assay. Data analysis was performed using R statistical software. Results The predominant malaria vector was An. funestus sensu lato (s.l.), which had an overall dye feeding rate of 11.2%. This was followed by An. gambiae s.l. at 3.5%. These corresponded to daily feeding rates of 4.8% and 1.2%, respectively. Sporozoite positivity rates were 2.3% (n = 29) in An. funestus s.l and 1.0% (n = 19) in An. gambiae s.l. Higher dye positivity was observed in male An. funestus (OR = 1.22; 95% CI = 1.03,1.46; P = 0.029) and male An. gambiae (OR = 2.20; 95% CI = 1.19,4.08; P = 0.015). Comparison of the impact of 2 versus 3 bait stations indicated no difference in feeding rates in either An. funestus (OR = 0.83; 95% CI = 0.40; 1.75), P = 0.624) or An. gambiae (OR = 1.11; 95% CI = 0.71, 1.71; P = 0.661). Conclusions The results from this study showed that predominant malaria vectors; Anopheles funestus led to a daily feeding rate that was presumed to be sufficient to cause a reduction in malaria incidence by ATSBs. There was no significant difference detected between deploying two or three bait stations per structure. The study provided important information utilized in the subsequent deployment of ATSBs in epidemiological trials.